2022
DOI: 10.1007/s00737-022-01268-y
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption habits and associations with anxiety or depressive symptoms postpartum in women with high socioeconomic status in Sweden

Abstract: Postpar tum depression and anxiety are common among new mothers. It is well-established that in the general population alcohol use is associated with depression and anxiety. Linking alcohol consumption to symptoms of postpartum depression (PPDS) or postpartum anxiety (PPAS) is presently less established. This study aims to determine if alcohol consumption pre-pregnancy, 6 weeks postpartum, 6 months postpartum, or changes in alcohol consumption are associated with PPDS or PPAS. Longitudinal data on 3849 women f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…This highlights the importance of routine monitoring of anxiety symptom severity by health professionals during the transition to motherhood, so that mothers receive appropriate support and preventative care. Despite growing evidence demonstrating a positive association between postpartum depression and drinking outcomes [37] , no such associations were evident in the current study. It may be possible that although postpartum depression is related to postpartum alcohol use, its impact or "net strength" may not be detectable above and beyond the effects of other variables.…”
Section: Principal Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…This highlights the importance of routine monitoring of anxiety symptom severity by health professionals during the transition to motherhood, so that mothers receive appropriate support and preventative care. Despite growing evidence demonstrating a positive association between postpartum depression and drinking outcomes [37] , no such associations were evident in the current study. It may be possible that although postpartum depression is related to postpartum alcohol use, its impact or "net strength" may not be detectable above and beyond the effects of other variables.…”
Section: Principal Resultscontrasting
confidence: 93%
“…Similarly, a recent general population study among Swedish mothers found that depressive symptoms at 6-weeks postpartum were positively associated with concurrent drinking, while there was no association between postpartum anxiety or drinking patterns at 6-weeks or 6months postpartum [37] . More research is clearly needed to improve our understanding of mental health correlates of problematic postpartum alcohol use to identify and target those at greatest risk.…”
Section: Mental Health Correlates Of Maternal Postpartum Alcohol Usementioning
confidence: 89%